Purification of Aqueous Solution from Ni (II) Ions Using Commercial and Bitter Orange Leaves Activated Charcoal - Jarullah, Areej. A; Alias, Mahasin. F; Hassan, Karim. H (Al-Nahrain Journal of Science, 2018)
The purification of diluted aqueous solution from toxic Ni (II) ion was investigated using commercial and bitter orange leaves activated charcoal as adsorbents through batch method. The contact times between the adsorbents and adsorbate at 298 K and pH of 5 were studied. The percentage metal removal approached equilibrium within 75 min on Commercial and 90 min on prepared charcoal surfaces. The experimental data of the metal removal equilibrium were correlated by either the Langmuir or Freundlich equations. Results indicate that the Langmuir model gave a better fit to the experimental data than the Freundlich equation. Kinetic processes of Ni2+ adsorption on Commercial and prepared charcoal were described by applying pseudo-first-order and pseudo-second-order rate equations which that the adsorption process obey pseudo-second-order rate equation.